'Sustaining Place' – a grounded theory of how informal carers of people with dementia manage alterations to relationships within their social worlds. Issue 3 (21st November 2012) - Daly, Louise; McCarron, Mary; Higgins, Agnes; McCallion, Philip
<x xml:space="preserve">Abstract</x> Aims and objectives This paper presents a theory explaining the processes used by informal carers of people with dementia to mange alterations to their, and people with dementias' relationships with and places within their social worlds. Background Informal carers provide the majority of care to people with dementia. A great deal of international informal dementia care research is available, much of which elucidates the content, impacts and consequences of the informal caring role and the coping mechanisms that carers use. However, the socially situated experiences and processes integral to informal caring in dementia have not yet been robustly accounted for. Design A classic grounded theory approach was used as it is designed for research enquiries that aim to generate theory illustrating social patterns of action used to address an identified problem. Methods Thirty interviews were conducted with 31 participants between 2006–2008. The theory was conceptualised from the data using the concurrent methods of theoretical sampling, constant comparative analysis, memo writing and theoretical sensitivity. Results Informal carers' main concern was identified as 'Living on the fringes', which was stimulated by dementia‐related stigma and living a different life. The theory of 'Sustaining Place' explains the social pattern of actions employed by informal carers to manage this problem on behalf of themselves and the person with dementia. Conclusions The theory of 'Sustaining Place' identifies an imperative for nurses, other formal carers and society to engage in actions to support and enable social connectedness, social inclusion and citizenship for informal carers and people with dementia. Relevance to clinical practice 'Sustaining Place' facilitates enhanced understanding of the complex and socially situated nature of informal dementia care through its portrayal of informal carers as social agents and can be used to guide nurses to better support those who live with dementia.